PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 015 BANJAR XII KABUPATEN ROKAN HILIR - Rimawati Rimawati; Hendri Mahardi; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of the problem in this research was conducted because of the low of IPS learning result of fourth grader of SD Negeri 015 Banjar XII, with the average of 58,8 class. The formulation of the problem